2014
DOI: 10.2341/12-349-l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fiber Inserts, Type of Composite, and Gingival Margin Location on the Microleakage in Class II Resin Composite Restorations

Abstract: This study evaluated the influence of fiber inserts, type of composites, and location of the gingival seat on microleakage in Class II resin composite restorations. Fifty noncarious human third molars were selected for the study. Standardized Class II box type cavities were prepared on the mesial and distal side of 45 teeth. The gingival margin was placed above the cementoenamel junction (CEJ) on the mesial side and below the CEJ on the distal side. The remaining five teeth received no cavity preparations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Results contradictory those of the present study have also been reported by Dhingra et al . and Belli et al ., in which no reduction in microleakage is shown. One reason for such contrasting results might be the difference in method of placing the restorations, or difference in type of fibers used.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Results contradictory those of the present study have also been reported by Dhingra et al . and Belli et al ., in which no reduction in microleakage is shown. One reason for such contrasting results might be the difference in method of placing the restorations, or difference in type of fibers used.…”
Section: Discussionmentioning
confidence: 86%
“…Light‐cure composites have become the material of choice as a direct posterior restorative material in clinical dentistry . This revolution is due not only because of their excellent esthetic properties, but also to their excellent workability, increased flexural modulus, increased depth of cure, and above all, their adhesion to dental tissues .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QTH Astralis 7 (Ivoclar, Vivadent, Lichtenstein) and LED Demetron A2 (Kerr, Donbury, Italy) were used for light-curing of composite resins at a light intensity of 1000 mW/cm 2 for 20 and 10 seconds, respectively. Table 1 presents the particulars of the materials used in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…1 Microleakage leads to recurrent caries, postoperative sensitivity, marginal discoloration and loss of the restoration. 2,3 Therefore, a large number of studies have been undertaken on techniques that result in a decrease in polymerization shrinkage, including placement of composite resins using the incremental technique, use of materials with low elastic modulus to absorb stresses and use of techniques to decrease the C-factor. 4-7 Since these techniques are time-consuming and increase the chair time, resin-based composite (RBC) manufacturers have made significant developments to reduce the shrinkage stress generated on light irradiation and today dentistry boasts of RBC filler technology that encompasses nanotechnology, 8 polymerization modulators technology 9 and non-methacrylate-based monomeric resin formulations.…”
Section: Introductionmentioning
confidence: 99%